Urban Renewal in the Monumental Area of Callao (Peru)? : An Analysis of the Fugaz Project Interventions in Four Different Dimensions - Mendoza Bazan, Brenda (2025)
AbstractThe article presents an approach to the Fugaz Project, an intervention carried out in the monumental area of Callao for commercial purposes and framed as an urban renewal initiative. This intervention triggered an interesting phenomenon due to the interaction of various actors who had not previously crossed paths and who now engage in a context where the residents of the monumental area find themselves in a position of subordination. The aim is to analyze how this urban intervention unfolded during a specific period (2015 to 2017) through four dimensions: the institutional and organizational arrangements that have facilitated the entry of a new economic actor into the area; socio-spatial fragmentation; the use of art to make the intervention attractive to both former residents and new visitors; and, finally, the experience and production of the place by the actors involved.